(untitled) (International Journal of Business Innovation, 2022)
In Madhesh Province of Nepal, 33.80 percent of municipalities have not passed the budget for the coming fiscal year 2021/22. For this to happen there may have some gaps and causes. To understand facts and suggest the way forward, this study was conducted. The study concluded that the local governments in Madhesh Province lack the provision of a participation mechanism. As practical implications, the lack of local participatory process has promoted very low outcomes than expected, access limit and domination to motivate people who may produce conflict and instability. Therefore, this paper has suggested to each municipality to establish a citizen engagement mechanism and build the capacity of citizens for stabilizing transparent and accountable governance.